1979
DOI: 10.1128/jb.137.1.490-501.1979
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and crystallization of ribulosebisphosphate carboxylase from autotrophically grown Rhodospirillum rubrum

Abstract: Serial culture of Rhodospirillum rubrum with 2% CO2 in H2 as the exclusive carbon source resulted in a rather large fraction of the soluble protein (>40%) being comprised of ribulosebisphosphate carboxylase (about sixfold higher than the highest value previously reported). Isolation of the enzyme from these cells revealed that it has physical and kinetic properties similar to those previously described for the enzyme derived from cells grown on butyrate. Notably, the small subunit (which is a constituent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 73 publications
3
27
0
Order By: Relevance
“…Furthermore, this increased activity is paralleled by an increase in the amount of Rbu-P2 carboxylase/oxygenase actually synthesized by the organism, with this enzyme produced at a level which represents up to 50% of the soluble protein under conditions of carbon dioxide deprivation. We further show that the adaptation occurs within the first transfer of heterotrophically grown cells to photolithotrophic growth conditions and not after 10 to 14 weeks of growth and transfer as previously reported (12). Such a response to nutrient (carbon dioxide) limitation is by no means unprecedented since various degrees of derepression of Rbu-P2 carboxylase/oxygenase synthesis have been observed in the hydrogen-oxidizing bacterium Alcaligenes eutrophus (7), the obligate chemolithotroph Thiobacillus neapolitanus (3), the cyanobacterium Anacystis nidulans (8), and the facultative autotroph Pseudomonas oxalaticus OXI (6).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, this increased activity is paralleled by an increase in the amount of Rbu-P2 carboxylase/oxygenase actually synthesized by the organism, with this enzyme produced at a level which represents up to 50% of the soluble protein under conditions of carbon dioxide deprivation. We further show that the adaptation occurs within the first transfer of heterotrophically grown cells to photolithotrophic growth conditions and not after 10 to 14 weeks of growth and transfer as previously reported (12). Such a response to nutrient (carbon dioxide) limitation is by no means unprecedented since various degrees of derepression of Rbu-P2 carboxylase/oxygenase synthesis have been observed in the hydrogen-oxidizing bacterium Alcaligenes eutrophus (7), the obligate chemolithotroph Thiobacillus neapolitanus (3), the cyanobacterium Anacystis nidulans (8), and the facultative autotroph Pseudomonas oxalaticus OXI (6).…”
Section: Discussionsupporting
confidence: 84%
“…Recently, it was reported that levels of Rbu-P2 carboxylase/oxygenase representing up to 40o of the soluble protein of R. rubrum may be obtained upon repeated transfer (10 to 14 weeks) of cells grown under a C02/H2 atmosphere (12). Thus, the levels of Rbu-P2 carboxylase/oxygenase obtained by these investigators in R. rubrum are similar to the levels found in the chloroplasts of eucaryotic cells.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Storage of extracts at -80°C was adequate for preserving activity over a few weeks, but for long term, the less convenient preservation in liquid N2 is required. Symbiodinium Rubisco is much more unstable than the Form II enzyme of R. rubrum, which is readily purified and, after purification, retains 50-70% of its activity after storage for 1 month at 4°C (Schloss et al 1979). The thermal sensitivity of carbon fixation in plants is generally the consequence of a lowered activation state of the Form I Rubisco caused by thermal instability of the AAA + motor protein, Rubisco activase (Portis 2003), which is, in turn, partially protected against elevated temperature by the GroEL-type chloroplast heat shock protein cpn60b (Salvucci 2008).…”
Section: Stability Of Extracted Rubiscomentioning
confidence: 99%
“…In addition, the results of this study specifically indicate that the T. intermedius enzyme is not the unique evolutionary octameric form of RuBPCase that was originally proposed (19,20,22), thus leaving R. rubrum as the only bacterial species with an independently confirmed 0-type enzyme (cf. 9,13,25,28).…”
Section: Results and Discussion Purification Of Rubpcase From T Intementioning
confidence: 99%